Four Members of Heat Shock Protein 70 Family in Korean Rose Bitterling (Rhodeus uyekii) - Kim, Jung Hyun (Dev Reprod, 2015)
Heat shock protein (HSP) 70, the highly conserved stress protein families, plays important roles in protecting cells against heat and other stresses in most animal species. In the present study, we identified and characterized four Hsp70 (RuHSP4, RuHSC70, RuHSP12A, RuGRP78) family proteins based on the expressed sequence tag (EST) analysis of the Korean rose bitterling R. uyekii cDNA library. The deduced RuHSP70 family has high amino acid identities of 72-99% with those of other species. Phylogenetic analysis revealed that RuHsp70 family clustered with fish groups (HSP4, HSC70, HSP12A, GRP78) proteins. Quantitative RT-PCR analysis showed the specific expression patterns of RuHsp70 family members in the early developmental stages and several tissues in Korean rose bitterling. The expression of 4 groups of Hsp70 family was detected in all tested tissue. Particularly, Hsp70 family of Korean rose bitterling is highly expressed in hepatopancreas and sexual gonad (testis and ovary). The expression of Hsp70 family was differentially regulated in accordance with early development stage of Rhodeus uyekii.